2004
DOI: 10.1509/jmkg.68.2.88.27787
|View full text |Cite
|
Sign up to set email alerts
|

Portfolios of Interfirm Agreements in Technology-Intensive Markets: Consequences for Innovation and Profitability

Abstract: Despite the high relevance of firms' portfolios of upstream interfirm agreements in technology-intensive markets, little is known about their impact on innovative success. The authors develop a conceptual framework that explains the consequences of different portfolio descriptors for radical innovation, incremental innovation, and profitability. An empirical test in the pharmaceutical industry shows strong support for the developed theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
229
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(245 citation statements)
references
References 66 publications
10
229
0
6
Order By: Relevance
“…Furthermore, the growing literature on inter-firm interaction in the pharmaceutical industry has mainly devoted attention to either large pharmaceutical firms (e.g., Wuyts, Dutta, & Stremersch, 2004) or start-up firms that face very specific challenges related to Stinchcombe's (1965) liability of newness hypothesis (e.g., Higgins & Gulati, 2006). In sum, a study of dedicated technology firms and their ability to license out their technologies would help bridge a void in prior literature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the growing literature on inter-firm interaction in the pharmaceutical industry has mainly devoted attention to either large pharmaceutical firms (e.g., Wuyts, Dutta, & Stremersch, 2004) or start-up firms that face very specific challenges related to Stinchcombe's (1965) liability of newness hypothesis (e.g., Higgins & Gulati, 2006). In sum, a study of dedicated technology firms and their ability to license out their technologies would help bridge a void in prior literature.…”
Section: Introductionmentioning
confidence: 99%
“…Radical innovation represents a dramatic departure from existing products in terms of technology and generate greater information processing and exposure to a variety of knowledge domains (Wuyts et al, 2004, Leifer et al, 2000. Scholars argue that internally generated knowledge provides low potential for creating radical innovation outputs (Rosenkopf and Nerkar, 2001) business environments (e.g., Salter, 2006, Lichtenthaler, 2009 (Chiang andHung, 2010, Subramaniam andYoundt, 2005).…”
mentioning
confidence: 99%
“…Apart from the size of an R&D partnership portfolio, its composition in terms of the mix of novel and repeat partners may also influence inward flows of technological knowledge (e.g., Wuyts et al, 2004). In uncertain environments, firms tend to engage in partnerships with firms they have collaborated with before (Gulati 1995).…”
Section: Portfolio Composition: Combining Novel and Repeat Partnersmentioning
confidence: 99%
“…Recent studies argue that R&D partnership portfolios, more than individual partnerships alone, represent key knowledge-gathering conduits that allow firms to leverage informational complementarities across their various R&D projects (Faems, van Looy, & Debackere, 2005;George, Zahra, Wheatley, & Khan, 2001;Munson & Spivey, 2006). Consistent with this view, several studies have shown empirical associations between R&D partnership portfolios and innovation (Powell et al, 1999;Rothaermel & Deeds, 2006;Soh, 2003;Stuart, 2000;Wuyts, Dutta, & Stremersch, 2004), while others have suggested a link between technological uncertainty and firms' proclivity to engage in multiple simultaneous R&D partnerships (Hagedoorn, 1993;Powell, Koput, & Smith-Doerr, 1996;Rosenkopf & Schilling, 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation